Selection of acid tolerant strains of phosphate-solubilizing bacteria in soils of Uttar Pradesh Himalaya - PAL, SUDHANSHU (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1993 to isolate and enumerate phosphate-solubilizing bacteria in 64 soil samples of various land use classes in soils of Uttar Pradesh Himalaya. Counts of potential indigenous phosphatesolubilizing bacteria ranged from 32-99 x 103/g soil and significantly correlated with organic matter, available phosphate, water-holding capacity and bulk density Of the 23 bacterial isolates, 14 were gram positive and 9 gram negative. An isolate (PAS 2) of pasture and waste land (PH 4.8) had higest phosphate-solubilizing capacity (63%) which tolerated a wide range of soil acidity (PH 4.5 -6.1). Seed inoculation of this isolate increased most probable number counts in rhizosphere and non-rhizosphtere soil samples of crops like maize (Zea mays L.), amaranth (Amaranthus hypochondriacus L.) and soybean (Glycine mex (L.) Merr.) and also available soil phosphorus. The isolate belonged to Bacillus sp.